2022
DOI: 10.12688/f1000research.123183.2
|View full text |Cite
|
Sign up to set email alerts
|

A general hypothesis of multistable systems in pathophysiology

Abstract: Despite intensive investigations numerous diseases remain etiologically puzzling and recalcitrant to treatments. A hypothesis is proposed here assuming that these difficulties are due to an unsuitable approach to the mechanisms of life, which is subjugated by an apparent complexity and fails to grasp the uniformity that lays behind. The stability of metabolism, despite the enormous complex of chemical reactions, suggests that reciprocal control is a prerequisite of life. Negative feedback loops have been known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The system consists of positive and negative loops, and we have demonstrated that it can globally behave as a monostable system (see Box 1 ) (when the negative loop is dominant) for stronger GABAergic transmission, or as a bistable system (when the positive loop is dominant) for a weakening of GABAergic transmission [ 18 ]. Bistable switches are known to promote predictable functional changes in living systems [ 26 ], also including pathogenesis processes [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system consists of positive and negative loops, and we have demonstrated that it can globally behave as a monostable system (see Box 1 ) (when the negative loop is dominant) for stronger GABAergic transmission, or as a bistable system (when the positive loop is dominant) for a weakening of GABAergic transmission [ 18 ]. Bistable switches are known to promote predictable functional changes in living systems [ 26 ], also including pathogenesis processes [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mutual inhibition between HPG and HPA axes gives rise to a positive loop; therefore, the dynamic system is a candidate multistable system that can admit multiple equilibria [ 130 ]. Hence, similarly to the thalamocortical loop, this endocrine loop can behave as a switch driving pathogenesis [ 27 ]. Such double-inhibitory loop operates physiological functions [ 72 , 131 ], but under peculiar circumstances could lead to functional disorders.…”
Section: Resultsmentioning
confidence: 99%